To solve the equation, we can start by simplifying both sides:
(g + 4) - 3g = 1 + g
First, let's remove the parentheses by distributing -3 to both terms inside:
g + 4 - 3g = 1 + g
Next, let's combine like terms on each side:
-2g + 4 = 1 + g
To isolate the variable on one side, let's move all terms with g to the left side by subtracting g from both sides:
-2g - g + 4 = 1
Simplifying further:
-3g + 4 = 1
To isolate the variable, let's move the constant term to the right side by subtracting 4 from both sides:
-3g = 1 - 4
Simplifying further:
-3g = -3
Finally, to solve for g, we divide both sides by -3:
g = -3 / -3
Simplifying the division:
g = 1
Now, let's check if the solution is correct by substituting g = 1 back into the original equation:
(g + 4) - 3g = 1 + g
Substituting g = 1:
(1 + 4) - 3(1) = 1 + 1
Simplifying both sides:
5 - 3 = 2
Simplifying further:
2 = 2
Since both sides of the equation are equal when g = 1, we can conclude that the solution is correct.
Therefore, the solution to the equation is g = 1.
Solve the equation. Check each solution by substituting it back into the original equation before submitting your quick check.
(g + 4) - 3g = 1 + g
(1 point)
O g= 1
O g=4
O no solution
• identity
1 answer